Lithium in the prevention of suicide in mood disorders: updated systematic review and meta-analysis. - Cipriani, A; Hawton, K; Stockton, S; Geddes, J (2013)
To assess whether lithium has a specific preventive effect for suicide and self harm in people with unipolar and bipolar mood disorders. Systematic review and meta-analysis. Medline, Embase, CINAHL, PsycINFO, CENTRAL, web based clinical trial registries, major textbooks, authors of important papers and other experts in the discipline, and websites of pharmaceutical companies that manufacture lithium or the comparator drugs (up to January 2013). Randomised controlled trials comparing lithium with placebo or active drugs in long term treatment for mood disorders. Two reviewers assessed studies for inclusion and risk of bias and extracted data. The main outcomes were the number of people who completed suicide, engaged in deliberate self harm, and died from any cause. 48 randomised controlled trials (6674 participants, 15 comparisons) were included. Lithium was more effective than placebo in reducing the number of suicides (odds ratio 0.13, 95% confidence interval 0.03 to 0.66) and deaths from any cause (0.38, 0.15 to 0.95). No clear benefits were observed for lithium compared with placebo in preventing deliberate self harm (0.60, 0.27 to 1.32). In unipolar depression, lithium was associated with a reduced risk of suicide (0.36, 0.13 to 0.98) and also the number of total deaths (0.13, 0.02 to 0.76) compared with placebo. When lithium was compared with each active individual treatment a statistically significant difference was found only with carbamazepine for deliberate self harm. Lithium tended to be generally better than the other active comparators, with small statistical variation between the results. Lithium is an effective treatment for reducing the risk of suicide in people with mood disorders. Lithium may exert its antisuicidal effects by reducing relapse of mood disorder, but additional mechanisms should also be considered because there is some evidence that lithium decreases aggression and possibly impulsivity, which might be another mechanism mediating the antisuicidal effect.